First union formation among the children of immigrants in Norway: Timing and choice of union type - Kenneth Aarskaug Wiik (Statistics Norway, Research Department, 2019)
Using Norwegian register data on all individuals born 1985 to 2000 who were either native-born or who immigrated as children or teens (N=1,013,734), the current study investigated timing of first co-residential union and choice of union type in the period 2005 through 2018. Descriptive results showed that 64% of the second generation (Norwegian-born children of immigrants) and 75% of the 1.5 generation (immigrated prior to age 18) chose cohabitation as first union, compared with 94% of those without a migration background. Results from competing risk event history models confirmed that second-generation immigrants, and particularly women, were more likely to marry directly and less likely to cohabit than those belonging to the 1.5 generation and Norwegians without a migration background. Second-generation individuals originating from Turkey, Pakistan, Morocco, Kosovo, Sri-Lanka, and India were more prone to marry directly than the native-born children of immigrants from other non-Western countries. Conversely, second-generation Iranians were less likely to marry, whereas those originating from Vietnam and Bosnia and Herzegovina were most likely to cohabit. The chance of marrying directly decreased across the study period among immigrant-background and majority individuals alike.
Keywords: J10; J12; J15; 330; First union formation; Cohabitation; Marriage; The Second generation; Immigrants; Norway